2013
DOI: 10.1111/jonm.12159
|View full text |Cite
|
Sign up to set email alerts
|

The effects of work alienation on organisational commitment, work effort and work-to-family enrichment

Abstract: Managers should increase the meaningfulness that people attach to their work, thereby maintaining a high-quality workforce. Possible strategies include: (1) improving person-job fit, (2) developing high-quality relationships, (3) better communicating the results people help to deliver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 59 publications
(101 reference statements)
7
82
0
4
Order By: Relevance
“…Literature claims that when organizational members have high level of trust to their organization and supervisor, they can pay more attention to their jobs (Tummers, Dulk, 2013). Therefore, it will bring extra profits for both themselves and their organization.…”
Section: Organizational Trustmentioning
confidence: 99%
“…Literature claims that when organizational members have high level of trust to their organization and supervisor, they can pay more attention to their jobs (Tummers, Dulk, 2013). Therefore, it will bring extra profits for both themselves and their organization.…”
Section: Organizational Trustmentioning
confidence: 99%
“…It is seen that studies made in business organizations towards work alienation focus on variables as organizational justice which affects work alienation and variables as organizational correlation, road stress, organizational identification, problem drinking behavior, job satisfaction, work centrality which can affect work alienation (Turan & Parsak, 2011;Tummers & Den Dulk, 2013;Sarros vd., 2002;Seybolt & Gruenfeld, 1976;Greenberg & Grunberg, 1995;Ceylan & Sulu, 2011;Efraty vd., 1991;Yalçın & Koyuncu, 2014;Tuna & Yeşiltaş, 2014;Sulu vd., 2010;Hirschfeld & Field, 2000;Yang vd., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[11,13,14] Moreover, Toode in 2014 and 2015 stressed that job-related anxiety is positively related with work withdrawal, and work frustration, but it has an inverse correlation with work motivation, satisfaction, and emotional gratification. [5,6,30] Likewise, Kudo in 2010 reported that in the introjected regulation type of motivation, the individual tries to do all behaviors to keep away from guilt feeling and anxiety or stress. [5,31] Therefore, motivation is adversely correlated with anxiety.…”
Section: Discussionmentioning
confidence: 99%